2021
DOI: 10.1016/j.talanta.2020.121468
|View full text |Cite
|
Sign up to set email alerts
|

Development of rapid colorimetric assay for the detection of Influenza A and B viruses

Abstract: The flu viruses are respiratory pathogens which, according to the World Health Organization (WHO), infect 5–10% of the world population resulting in 3–5 million cases of severe illness and 290,000 to 650,000 annual deaths. Early diagnosis and therapeutic intervention can ameliorate symptoms of infection and reduce mortality. The conventional diagnosis of viral infections, including flu viruses, has evolved over the years with diverse approaches, however, there are inherent short comings associated with these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the past couple of years, viral isolation, serology, nucleic amplification, and lab-on-chip assays have been used and modified for Flu viruses' diagnostics. However, due to the common drawbacks of these diagnostic measures and the overwhelming concerns associated with mortality rates, there continues to be a need for rapid diagnostic tools for Flu viruses [52] , [63] . Raji et al reported the development of biosensors for the detection of Flu A and Flu B viruses [52] .…”
Section: Biosensors For the Detection Of Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past couple of years, viral isolation, serology, nucleic amplification, and lab-on-chip assays have been used and modified for Flu viruses' diagnostics. However, due to the common drawbacks of these diagnostic measures and the overwhelming concerns associated with mortality rates, there continues to be a need for rapid diagnostic tools for Flu viruses [52] , [63] . Raji et al reported the development of biosensors for the detection of Flu A and Flu B viruses [52] .…”
Section: Biosensors For the Detection Of Pathogensmentioning
confidence: 99%
“…However, due to the common drawbacks of these diagnostic measures and the overwhelming concerns associated with mortality rates, there continues to be a need for rapid diagnostic tools for Flu viruses [52] , [63] . Raji et al reported the development of biosensors for the detection of Flu A and Flu B viruses [52] . This study used antibodies for Flu A and Flu B viruses and immobilized them on the surface of colorimetric biosensors.…”
Section: Biosensors For the Detection Of Pathogensmentioning
confidence: 99%
“…These nanoparticles are applied to increase the sensitivity and effectiveness in detecting microorganisms, reducing time, costs, and the need for advanced laboratory structures to perform the diagnosis (Jain et al, 2020;Landry et al, 2017;Li et al, 2018;Safarpour et al, 2021). Immunoagglutination using gold (AuNP) and DNA probes immobilization on surfaces coated with metallic nanoparticles (AuNPs and MNPs) where the DNA probe on the surface of AuNPs was a signal reporter by fluorescence are some examples of this application (Raji et al, 2021).…”
Section: Nanoparticles For Biosensor Constructions In the Diagnosis And Detection Of Infectious And Noninfectious Diseasesmentioning
confidence: 99%
“…The immunoassay test from the association of metallic nanoparticles was reported with monoclonal antibodies that bind conjugately to epitopes (molecules, DNA, cells) of the microorganism on a surface with an affinity to the antibody (Basu et al, 2004;Basso et al, 2018;Mikaelyan et al, 2017). This surface contains antibodies specific for the antibody associated with the nanoparticle, which retains them and allows visualization by colorimetric change (Raji et al, 2021). This association has shown to be a promising platform for outbreak elucidation and diagnosis of various agents (Bhattarakosol, et al, 2018;Chen et al, 2018;Chen et al, 2019;Elahi et al, 2019;Vedova-Costa et al, 2021), as well as monitoring the evolution of neurodegenerative diseases such as Alzheimer's and diabetes (Popli et al, 2018).…”
Section: Nanoparticles For Biosensor Constructions In the Diagnosis And Detection Of Infectious And Noninfectious Diseasesmentioning
confidence: 99%
“…Cotton swabs have been recently used in the fabrication of immunoassays for the detection of different pathogens. In these assays, the colorimetric detection was achieved based on visual discrimination of the color change. These assays are simple, fast, and easy to perform.…”
Section: Introductionmentioning
confidence: 99%